1992
DOI: 10.1111/j.1744-7348.1992.tb03991.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of barley yellow dwarf virus by field collected aphids (Homoptera: Aphididae) and their relative importance in barley yellow dwarf epidemiology in southwestern Idaho

Abstract: Populations of cereal aphids were sampled from 1985-1988 and assayed for transmission of barley yellow dwarf virus (BYDV). Rhopalosiphum padi, Rhopalosiphum rnaidis, Sitobion avenue, Metopolophiurn dirhodum, Schizaphis graminurn and Macrosiphum euphorbiae collected from host plants transmitted BYDV in bioassays. Of the 1028 Diuraphis noxia collected from plants, one may have transmitted BYDV. The isolate involved resembled SGV in serological and biological characteristics, but since it was not recoverable by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…This percentage is in close agreement with the Þndings of Chapin et al (2001) and Halbert et al (1992a), who found that Ϸ3% of Þeld collected aphids were viruliferous over a 3-and 4-yr study, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This percentage is in close agreement with the Þndings of Chapin et al (2001) and Halbert et al (1992a), who found that Ϸ3% of Þeld collected aphids were viruliferous over a 3-and 4-yr study, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Despite being an efÞcient vector of Barley yellow dwarf virus-PAV and Cereal yellow dwarf virus-RPV (Gray et al 1998), R. rufiabdominale from South Carolina was not considered an important vector of yellow dwarf viruses due to the absence of correlation between R. rufiabdominale population and yellow dwarf incidence (Chapin et al 2001). However, surveys of aphid vectors of yellow dwarf viruses in the United States showed that R. padi density is usually correlated with Barley yellow dwarf virus Þeld incidences (Halbert and Pike 1985, Halbert et al 1992a, Chapin et al 2001. In this study the frequency of viruliferous vector detection is too low to establish the relative importance of each species as yellow dwarf virus vectors in our area of study, but it is clear that both aphids are capable of introducing Barley yellow dwarf virus-PAV and Cereal yellow dwarf virus-RPV into wheat Þelds in Alabama and western Florida.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that average densities over 20 aphids per plant can cause substantial losses of yield and quality of wheat (Basky & Fónagy, 2003). There are also indirect damages including excretion of honeydew from aphids and as a vector of viruses, most notably two strains of the Luteovirus Barley Yellow Dwarf Virus (BYDV-MAV and BYDV-PAV) (Susan et al, 1992). To prevent the occurrence and prevalence of aphid, large amounts of insecticides are used, causing environment pollution.…”
Section: Detecting and Discriminating Winter Wheat Aphid By Remote Sementioning
confidence: 99%